When happy people make society unhappy: Emotions affect tax compliance behavior - Hechtner, Frank; Mohr, Peter; Fochmann, Martin; Kirchler, Erich (Journal of Economic Behavior & Organization, 2025)
Emotions affect judgments and decision making. Our paper presents a study to show that incidental background emotions (i.e., emotions not related to the actual decision) influence individuals’ tax compliance attitudes and behavior. A large-scale survey of 22,220 German taxpayers and a controlled laboratory experiment provide evidence that positive background emotions reduce willingness to comply compared to aversive (negative) background emotions. The participants in our survey show less favorable tax compliance attitudes on weekends, which are usually associated with more positive background emotions. These findings are supported by the results of a controlled laboratory experiment in which background emotions were induced by standardized pictures. Individuals choose to evade taxes more often after being exposed to positive emotions than after being exposed to aversive emotion
CRIS-Team Scopus Importer:2025-01-31
Keywords: Compliance attitudes; Compliance behavior; Emotions; Experimental economics; Tax evasion